(untitled) (TAJ: Journal of Teachers Association, 2009)
Myocardial Infarction (Ml) is the most common form of heart disease and the single most important cause of premature death in the developed and developing world. Unfortunately the incidence of the condition is increasing rapidly in many developing countries like Bangladesh. Effort should therefore be taken to minimize the risk factors of Ml. There are several studies which evaluate the relation of serum ferritin with Ml in abroad. In Bangladesh, there is no such study was carried out to evaluate the relationship between serum ferritin and Ml. So the present work has been designed to evaluate the association of serum ferritin with Ml. The present study was carried out in the Department of Biochemistry, BSMMU in collaboration with Department of Cardiology, BSMMU and NICVD, Dhaka during the period of July 2001 to December 2002. A total of 50 subjects were selected, Group A ( 20 subjects of Ml) and Group B (30 subjects of Control). The mean level of serum ferritin in control subjects were 111.65 ± 50.47 ng/ml and in test subjects were 258.44 ± 87.87 ng/ml. So the present study showed that serum ferritin level is significantly higher in patients with Ml. From the present study, it is difficult to draw any definite conclusion but suggested that high serum ferritin concentration may be a cause of the incidence of Ml. doi: 10.3329/taj.v16i1.3893 TAJ June 2003; Vol.16(1): 5-7